Characterization of Microplastics in Total Atmospheric Deposition Sampling from Areas Surrounding Industrial Complexes in Northwestern Colombia (2022)
In this study, the total atmospheric deposition of microplastics in places near an industrial complex in Cartagena, Colombia is evaluated by taking samples at three points at different distances from the industrial zone. The samples obtained were treated to quantify and identify the type of plastic present, indicating the presence of polystyrene, polypropylene, polyethylene, polyvinyl chloride, and polyethylene terephthalate. The values of microplastics obtained were related to the climatic conditions of the areas (wind and rainfall) to determine these effects on the transport of microplastics. Values of 9472 ± 702 MP were obtained at the point closest to the industrial area and 1455 ± 14 MP at the farthest point, within which a greater proportion were fibers. In this study, it was also possible to determine that the microplastics most affected by the wind were the fragments. © 2022 by the authors.